NARRATIVE REVIEW KONSELING KELOMPOK STRATEGI MIND MAPPING BERBASIS MINDMAPLE LITE: UNTUK MENINGKATKAN SELF REGULATION - Hijrah Eko Eko Putro; Hasna Nur Afifah; Nursidah Ria; Linda Sulistiyowati (UIN Sunan Kalijaga Yogyakarta, 2021)
Guidance and Counseling is a service by providing assistance to individuals either individually or in groups to be able to independently and develop optimally. Guidance and Counseling services are needed in schools to help develop the potential of students in schools. Therefore, it is really necessary to collaborate with the roles of many parties, one of which is the counseling guidance teacher. Guidance Counseling teacher’s role to improve self regulation including by using a mind mapping strategy-based group counseling service mindmaple lite. In this narrative review discusses the effectiveness of strategy group counseling mindmapping based mindmaple lite in improving self regulation students. Search for articles was carried out on the database google scholar using the keyword “technical group counseling mindmapp”, “ Group Counseling to improve self regulated”, “Technique mindmapp to improve self regulation”. Articles used in the preparation narative review. This is an article published in the last 10 years, for the number of articles obtained there are 7 articles used. From the narrative review, it is found that the strategy group counseling mind mapping based indmaple lite can be used to improve self regulation in students.